(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Strategic activities to ensure innovation processes, combining the development, direct production and distribution of new products, aimed primarily at improving the company’s products, interaction with consumers, search and expansion of new markets ets. From these perspectives, evaluating a distribution management strategy that meets the needs and demands of consumers is an important step in improving a company’s efficiency. The article evaluates the strategy of managing the distribution of innovative products in the marketing logistics of a chemical company from the standpoint of consumers on the basis of a qualimetric approach. According to the results of the evaluation, it was found that the strategy needs to be improved by increasing the rate of profit compared to the rate of price growth. There is also a set of recommendations for improving the strategy of managing the distribution of innovative products in marketing logistics in accordance with the prospects of the consumer, which is the basis for the methodology of choosing the most objective strategic alternative in a chemical company. The object of research is the process of evaluating the strategic activities of the distribution management by innovative products. The information base consists of information-analytical reports of the chemical industry company, scientific works of domestic and foreign scientists in the field of marketing logistics, innovation marketing and innovation management, data collected by the author of the chemical industry. In the study, the author used a qualimetric approach, the Spearman rank correlation coefficient. The obtained results can be further used for research and comparison of other industrial enterprises in different industries.